1999
DOI: 10.1016/s0002-9440(10)65496-x
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Mutations Are Frequent in Human Hepatocellular Carcinomas Associated with Hepatitis C Virus Infection

Abstract: Hepatocellular carcinoma (HCC) is one of the most common fatal cancers worldwide. Hepatitis B virus and hepatitis C virus infections, exposure to aflatoxin, and excessive intake of alcohol have been identified as major risk factors. However, the molecular mechanisms underlying their development are still poorly understood. Recently, beta-catenin, one of the key components of the Wnt signaling pathway, has been found to be mutated in about 20% of HCCs, suggesting a role of the Wnt pathway in their development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
173
4
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 256 publications
(186 citation statements)
references
References 40 publications
8
173
4
1
Order By: Relevance
“…In our study, CTNNB1 mutations (S37Y, S37P, D32E, and D32G) were found in two primary CM and in one metastatic melanoma, and these point mutations were similar to those previously reported by Huang et al (24). The mutations in codon 37 involve the sequence for GSK-3␤ phosphorylation, implicated in the down-regulation of ␤-catenin through phosphorylation of serine residues.…”
Section: ␤-Catenin and Tumor Progression In Melanoma (A Demunter Et supporting
confidence: 90%
“…In our study, CTNNB1 mutations (S37Y, S37P, D32E, and D32G) were found in two primary CM and in one metastatic melanoma, and these point mutations were similar to those previously reported by Huang et al (24). The mutations in codon 37 involve the sequence for GSK-3␤ phosphorylation, implicated in the down-regulation of ␤-catenin through phosphorylation of serine residues.…”
Section: ␤-Catenin and Tumor Progression In Melanoma (A Demunter Et supporting
confidence: 90%
“…β-catenin, as a part of E-cadherin/catenin complex, is involved in two major functions: cell adhesion and transmission of the proliferating signal of the Wingless/Wnt pathway. β-catenin mutation in exon 3 activate the gene itself in HCCs [15], [16], [33]. However, the mutation of this gene is rare in those HCC with allelic loss of 16q21-q23 as evidenced from data in this paper.…”
Section: Discussionmentioning
confidence: 78%
“…Results of previous studies showed a variation of p53 mutations from various areas in terms of frequency, spectrum and timing: mutation of codon 249 is associated with AFB1 exposure in rural regions of China (Qidong) and Africa (Mozambique and Senegal) and may represent an early event during hepatocarcinogenesis, whereas different mutation spectrum of p53 was observed in Japan and big cities of China(Shanghai and Beijing) [11][12][13]. In addition, activation or DNA amplification of c-myc and cyclin D, mutations of β-Catenin and IGFIIR/M6P have been observed in HCC [14][15][16]. Another approach to find the genes associated with HCCs is to screen for regions with frequent genetic alteration by using whole-genome scanning technologies including microsatellite analysis (MSA) and comparative genomic hybridization (CGH).…”
Section: Introductionmentioning
confidence: 99%
“…b-Catenin mutations were found in 13-43% of the cases, depending on the series (de La Coste et al, 1998;Huang et al, 1999;Legoix et al, 1999;Nhieu et al, 1999;Terris et al, 1999;Hsu et al, 2000;LaurentPuig et al, 2001). Biallelic inactivations of AXIN1 through mutations associated with loss of heterozygosity or homozygous deletion are observed in 5-8% of the HCCs (Satoh et al, 2000;Laurent-Puig et al, 2001).…”
mentioning
confidence: 99%